Second Binormal Motions of Inextensible Curves in 4-dimensional Galilean Space - Korkmaz, Fatma Bulut; Bektas, Mehmet (Walter de Gruyter Gmbh, 2020)
In our study, we give the associated evolution equations for curvature and torsion as a system of partial differential equations. In addition, we study second binormal motions of inextensible curves in 4-dimensional Galilean space.
Keywords: inextensible curves; second binormal motions